2004
DOI: 10.1021/cm035348i
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Thermal Properties on the Copolymer Sequence in Diacetylene-Containing Polycarboranylenesiloxanes

Abstract: Diacetylene-containing polycarboranylenesiloxane copolymers were prepared by two different methods to yield either alternating or block copolymers with respect to the diacetylene distribution along the backbone. With each method, a set of copolymers was prepared with trisiloxane:carborane:diacetylene molar ratios of 10:9:1, 5:4:1, and 3:2:1. Both sets of copolymers yielded networks upon thermal curing. Even though the two methods produced materials of comparable molecular weights and overall compositions, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 15 publications
(17 reference statements)
0
32
0
Order By: Relevance
“…When heated in air to 8008C, no additional weight loss was observed. For comparison, Kolel-Veetil et al 14 reported that for diacetylene-containing polycarboranylenesiloxanes, the temperature resulting in 10% weight loss (Td 10 ) in nitrogen is in the range of 623-5558C and char yield at 10008C is from 46 to 70% according to diacetylene content and copolymer sequence. From aforementioned, the high thermal and oxidative stability of PACS make it potentially useful as high performance matrix resin and precursor for ceramics.…”
Section: Thermal and Oxidative Propertymentioning
confidence: 99%
“…When heated in air to 8008C, no additional weight loss was observed. For comparison, Kolel-Veetil et al 14 reported that for diacetylene-containing polycarboranylenesiloxanes, the temperature resulting in 10% weight loss (Td 10 ) in nitrogen is in the range of 623-5558C and char yield at 10008C is from 46 to 70% according to diacetylene content and copolymer sequence. From aforementioned, the high thermal and oxidative stability of PACS make it potentially useful as high performance matrix resin and precursor for ceramics.…”
Section: Thermal and Oxidative Propertymentioning
confidence: 99%
“…14,15 Recently, several investigations have been conducted on polymers containing siloxane and acetylene units. [16][17][18][19][20][21][22][23][24] For example, Keller 17 and coworkers reported the preparation of linear siloxane-diacetylene polymers by reacting dichlorosiloxanes with dilithiodiacetylene. These linear silxoane-diacetylene polymers show excellent thermal and thermooxidative stabilities.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve any appreciable extent of curing, the films (cast on a NaCl IR disk) had to be irradiated with UV radiation for an extended period (several days). The same level of cure could be achieved more rapidly (in about 2 hours) under harsher thermal cure conditions (250-400°C) (7). The slowness of the UV-curing could be attributed to a lack of proximal ordering/stacking of the diacetylene centers, which results in the enhancement of the rate of solid state polymerization by irradiation in the solid phase (//).…”
Section: Resultsmentioning
confidence: 99%
“…In the aerospace industry, the need especially for high temperature elastomers, plastics, and ceramics that have thermal, thermo-oxidative, and hydrolytic stability and that can also maintain flexibility to well below ambient temperatures is severe. In this regard, the linear polymers of carboranylenesiloxanes ( Figure 1) stand out as excellent candidates due to their exceptional thermal, thermo-oxidative, and elastic properties (7). The properties of these linear polymers may be enhanced further by their conversion into extended network polymers.…”
mentioning
confidence: 99%